Innovative teaching in a new normal - Gibbs, Keziah; Pyman, Hannah (Septentrio Conference Series, 2021)
With 2020 bringing unprecedented circumstances for us all, at the University of Essex we’ve been striving to move our previously in-person information literacy and research support teaching online. In doing this, we wanted to see the unexpected situationasan opportunity for improvement and increased engagement. This has required innovation and creativity, and has led us to deliver our training in a range of different formats. These formats include: online tutorials, YouTube videos, virtual workshop sessions, and mixed-media webpages using Springshare’s LibGuides software. By using a variety of solutions to reach our users, we have seen take-up for our teaching offer increase beyond our previous numbers. We believe this is in no small part due to our online resources’ ability to reach students in various locations and situations, including those working across campuses, outside of the UK, and those who may have other commitments alongside their studies. As well as this, we have been able to increase the accessibility of our teaching by ensuring our newly created online teaching materials meet UK web accessibility standards. In this presentation, we will share the lessons we have learnt in our shift to online teaching. We will explore the different technologies used to achieve this, discussing what has and hasn’t worked in our aim to increase the scope and interactivity of our information literacy and research support training. We will include feedback from participants, and will explore how we intend to broaden our offer further in the future. Ultimately, our presentation will demonstrate how the unusual situation of 2020 led us to innovate in newand interestingways.